Acute Pancreatitis Presenting with Polyarthritis and Intraosseous Fat Necrosis: A Case Report - Hilal Kocabaş; Meltem Alkan Melikoğlu; İlhan Sezer and Ülkü Gürbüz and Cahit Kaçar and Bülent Bütün (Archives of Rheumatology, 2010)
Polyarthritis and panniculitis can be the presenting manifestations of pancreatitis. Early recognition of this triad is critical because of the high mortality rate from pancreatic disease when the diagnosis is delayed. Although this association can be seen at any age, its frequency peaks around the fifth decade of life. We report this case because of the rarity of the association and the high morbidity and mortality in these patients. (Turk J Rheumatol 2010; 25: 221-4)